Transfer models and commercialization strategies of technologies in colombian universities - Toro Galvis, Juana María; Ocampo López, Olga Lucía; Vergara Quintero, María del Carmen (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The transfer of knowledge and technology is a process that allows the exchange of scientific or social knowledge, generated from the academic to productive sectors, with the purpose of strengthening a relationship between the university, business, state and civil society. The research sought to investigate in 12 universities of the Colombian Coffee Region about the models and strategies used in the knowledge and technology transfer process. The results allow us to identify that 33% managed to have some type of successful transfer such as direct sales, cooperation agreements or technological alliances. Licensing, Spin off or Start up are still incipient.